Forests of Madhya Bharat - Sondhi, G. S. (Indian Forester, 1954)
The Madhya Bharat Forest Department, with its numerous problems, came into existence in 1948. The forests are mostly Tropical Deciduous with a variety of forest produce and wildlife. Most of the tree crop is ruined due to over exploitation. New working plans are to be prepared for some forests. The old ones are to be revised on the basis of Silvicultural research. Regeneration is mostly through repeated coppice, with few plantations. The 'Vana Mahotsava' has given impetus to "extension forestry". Soil conservation work is confined to anti-erosion and afforestation works. Uplift of forest village population, particularly Adivasis, is given due attention. Under the Five-Year Plan schemes, the forests are developing all round.